Sugar mill, Trinidad, W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
Photo of a sugar mill in Trinidad. A handwritten correspondence on the card notes this sugar mill as Brechin Castle Estate and one of the largest sugar factories in Trinidad. No. DT77835B.
Colour: Green, Yellow and Brown Hues ; Style: Landscape ; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Sugarcane; Sugar factories